Individualized treatment of chronic hepatitis C with pegylated interferon and ribavirin - Roberto J Carvalho-Filho; Olav Dalgard (Dove Medical Press, 2010)
Roberto J Carvalho-Filho1, Olav Dalgard21Division of Gastroenterology, Hepatitis Section, Federal University of São Paulo, São Paulo, Brazil; 2Department of Medicine, Rikshospitalet, Oslo, NorwayAbstract: Chronic infection with hepatitis C virus (HCV) is a major public health problem, with perhaps 180 million people infected worldwide. A significant proportion of these will eventually develop clinical complications, such as cirrhosis, liver decompensation and hepatocellular carcinoma. Sustained virological response (SVR) to antiviral therapy is associated with improvement in liver histology and survival free of liver-related complications. Great effort has been made to improve SVR rate by adapting the duration of therapy according to HCV genotype and to on-treatment response. Rapid virological response (RVR, undetectable HCV RNA at week 4) usually has a high positive predictive value for achieving SVR and early virological response (EVR, ≥ 2 log reduction or undetectable HCV RNA at week 12) exhibits a high negative predictive value for non-response. Individualized approach can improve cost-effectiveness of HCV antiviral therapy by reducing side effects and the costs of therapy associated with unnecessary exposure to treatment and through extending therapy for those with unfavorable features. This article summarizes recent data on strategies of individualized treatment in naïve patients with mono-infection by the different HCV genotypes. The management of common side effects, the impact of HCV infection on health-related quality of life and the potential applications of host genomics in HCV therapy are also briefly discussed.Keywords: hepatitis C, pegylated interferon, individualized treatment, genotype, genomics